Statistics for research with a guide to SPSS - George Argyrous (Sage, 2011)
From the publisher. This fully updated edition of Statistics for Research explains statistical concepts in a straight-forward and accessible way using practical examples from a variety of disciplines. If you're looking for an easy-to-read, comprehensive introduction to statistics with a guide to SPSS, this is the book for you!